Consultative WorkshopThe Role of Climate Information Data and Services in Climate Risk Management in Uzbekistan and event dedicated to World Soil Day and World Mountain Day - Anarbekov, Oyture (2023)
Brochure and programme info for the Consultative workshop on the role of climate information data and services in climate risk management held in Uzbekistan, 5 Dec 2022.